Synthesis and Antiviral Evaluation of 5-(4-Aryl-1,3-butadiyn-1-yl)-uridines and Their Phosphoramidate Pronucleotides - Evan Saillard; Otmane Bourzikat; Koffi Assa; Vincent Roy; Luigi A. Agrofoglio (Molecules)
The emergence of RNA viruses driven by global population growth and international trade highlights the urgent need for effective antiviral agents that can inhibit viral replication. Nucleoside analogs, which mimic natural nucleotides, have shown promise in targeting RNA-dependent RNA polymerases (RdRps). Starting from protected 5-iodouridine, we report the synthesis of hitherto unknown C5-substituted-(1,3-diyne)-uridines nucleosides and their phosphoramidate prodrugs. The modifications at C5 include 4-(trifluoromethyl)benzene (a), 4-pentyl-benzene (b), 3,5-dimethoxy-benzene (c), 4-(trifluoromethoxy)benzene (d), 3-aniline (e), 4-pyridine (f), 3-thiophene (g), C6H13 (h), 2-pyrimidine (i), cyclopropyl (j), and phenyl (k) groups. These compounds were synthesized using Sonogashira palladium-catalyzed reactions and nickel–copper-catalyzed C-H activation between various alkynes, yielding between 25% and 67%. The antiviral activities of obtained compounds were measured through HTS against RNA viruses including influenza H1N1 and H3N2, human respiratory syncytial virus (RSV), SARS-CoV-2, Zika, hepatitis C virus (HCV), Hepatitis E virus (HEV), as well as against coronavirus (HCoV-229E). Unfortunately, none of them showed promising antiviral activity, with less than 85% inhibition observed in the cell viability screening of infected cells.